A disconnect between classroom and professional writing: we are not teaching public health students to write effective titles. (4th March 2020) - Anderson, Olivia; August, Ella
ABSTRACT: Titles are considered a crucial element of grant applications, journal articles, reports and other public health documents, but they are often overlooked in student writing assignments. In this article, we argue that public health instructors should teach students how to write compelling document titles. Our argument about titles is part of a broader assertion that public health students should be asked to write in professional formats such as grant applications, reports and journal articles. Requiring students to engage with important writing conventions like titles that are used in the professional workplace helps them make connections between the content they are writing about and the activities, roles, values and context of public health practice. We recommend that instructors explicitly incorporate titles into their assigned writing in three ways: first, instructors should require titles; second, instructors should provide criteria for a good title that are appropriate to the document type and finally, instructors should award points for a good title.